2022
DOI: 10.3389/fbioe.2022.883335
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Activity of an Anodized TiNbSn Alloy Prepared in Sodium Tartrate Electrolyte

Abstract: In this study, we anodized a TiNbSn alloy with low Young’s modulus in an electrolyte of sodium tartrate with and without hydrogen peroxide (H2O2). The photo-induced characteristics of the anodized alloy were analyzed for crystallinity and electrochemical conditions with comparisons to the effect with the addition of H2O2. The antibacterial activity was evaluated using methicillin-resistant Staphylococcus aureus and other pathogenic bacteria according to ISO 27447, and time decay antibacterial tests were also c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 39 publications
1
11
0
Order By: Relevance
“…Osteoblast progenitor cells are expressed in the endosteum of the bone marrow [36]. The TNS alloy after anodic oxidation treatment promotes bone formation by proliferating and activating osteoblasts in the endosteum of the bone and exerts an antibacterial effect through photocatalytic performance owing to sodium tartrate [48,49]. The TNS alloy is considered to be a promising orthopaedic implant material owing to the low Young's modulus and functional improvement by surface modi cation.…”
Section: Discussionmentioning
confidence: 99%
“…Osteoblast progenitor cells are expressed in the endosteum of the bone marrow [36]. The TNS alloy after anodic oxidation treatment promotes bone formation by proliferating and activating osteoblasts in the endosteum of the bone and exerts an antibacterial effect through photocatalytic performance owing to sodium tartrate [48,49]. The TNS alloy is considered to be a promising orthopaedic implant material owing to the low Young's modulus and functional improvement by surface modi cation.…”
Section: Discussionmentioning
confidence: 99%
“…The intensity of the radiated light was 1.0 mW/cm 2 at the surface of the cell comprising the MB solution (3.19 ppm) and anodized alloy. The photocatalytic activity was evaluated by measuring the absorbance of MB at 664 nm using a UV-vis spectrophotometer (Jasco V-550, JASCO Corporation, Tokyo, Japan) [ 25 , 30 ]. The photogenerated hydroxyl radicals (•OH) react with terephthalic acid (TA) in a disodium terephthalate (NaTA) solution, thereby producing 2-hydroxyterephthalic acid (HTA) via a hydroxylation reaction, as shown in the following Equation (1): C 6 H 4 (COOH) 2 + •OH→C 6 H 4 (COOH) 2 OH …”
Section: Methodsmentioning
confidence: 99%
“…Anodic oxides, prepared using the electrolytes of acetic or sulfuric acid aqueous solutions, improved the osseointegration owing to the formation of hydroxyapatite in an experimental model, thereby demonstrating the efficacy of the surface improvement on the biocompatibility of TiNbSn alloys [ 19 , 20 , 21 , 22 , 23 ]. Furthermore, the photocatalytic and antimicrobial activities under UV illumination were confirmed in the anodized TiNbSn alloys, prepared in an electrolyte of sodium tartrate aqueous solution [ 24 , 25 ]. In previous studies, clinical and preclinical studies have shown that the low Young’s modulus of TiNbSn alloys improves stress shielding, which is useful in reducing bone atrophy and promoting bone healing.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The photocatalytic and antibacterial performances of anodized TiNbSn alloys prepared in an electrolyte of sodium tartrate acid have been studied [ 68 , 69 , 70 , 71 ]. In the development of antibacterial metals, antibacterial metal ions, such as silver and copper, and antibacterial agents, such as iodine and vancomycin, have been used [ 72 , 73 , 74 , 75 ].…”
Section: Photocatalytic Activity Of Anodized Tinbsn Alloymentioning
confidence: 99%